THE MECHANISM OF CURRENCY REGULATION IN MODERN CONDITIONS: THEORETICAL ASPECT - K. G. Bunevich; T. A. Gorbacheva (Вестник университета)
One of the important factors for improving the economic situation in the Russian Federation is the optimization of the mechanism of currency regulation. Its role as the main means of implementing monetary policy is of particular importance in countries where the national currency has limited convertibility, since it is not in stable demand in the global financial markets. The purpose of this article is to summarize existing theoretical approaches to the problem of formation and regulation of the exchange rate based on the study of the evolution of relevant theories and concepts, as well as the definition of their scope of application and the conditions of validity. The article systematizes the theoretical aspects of the formation and regulation of the exchange rate. The paper highlights the instruments that affect the exchange rate. The authors study the main approaches to the relationship between the balance of payments and the exchange rate. The obtained theoretical results can be used in the formation and adjustment of monetary policy.